Design Of Property Sales Information System PT.Quality Property Indonesia - Sudarto, Ferry; Mulyati, Mulyati; Harahap, Eka Purnama; Nurul, Fira Arbaimaniar (APTISI Transactions on Management (ATM), 2020)
In the property business, this company can help provide a place for long-term business and investment. In this discussion the property sales system used is to use SWOT, so that it can help stakeholders in make decisions. In this case the author uses several methods including research methods, analysis methods, design methods, testing methods. Where the research methods in the form of observation, interviews, literature studies. The analysis method which uses SWOT analysis. The design method uses a design model using UML (Unified modeling language), PHP a database using MYSQL, and browser using Google Chrome. The testing method uses a blackbox. In this case the researchers have several objectives in conducting research in this thesis including To facilitate marketing to market property products sold by entering the list of properties to be sold, To help the process of buying and selling transactions quickly, precisely, and safely, To help process sales reports . Then the results customer will easily find the property to be purchased, Easing the burden on admin staff in the process of buying and selling property, Can speed up sales reports and can reduce errors in recording reports.